Serum exosomal circCCDC66 as a potential diagnostic and prognostic biomarker for pituitary adenomas - Yue, Xiao; Lan, Fengming; Liu, Weiping (Frontiers in Oncology, 2023)
Purpose: Circular RNAs (circRNAs) play an important role in tumorigenesis and exosomal circRNAs have the potential to be novel biomarkers for cancer diagnosis. Here, we are committed to reveal serum exosomal circCCDC66 as a noninvasive biomarker to diagnose and predict recurrence in pituitary adenoma (PA).Methods: 90 PA patients and 50 healthy subjects were enrolled for clinical validation. Exosomes were extracted from the serum and validated by transmission electron microscopy, nanoparticle tracking analysis and western blot assay. The expression of circCCDC66 in serum exosomes was assessed using quantitative real-time PCR (qRT-PCR), and correlations between circCCDC66 expression and clinicopathological factors were analyzed. The reliability of serum exosomal circCCDC66 to diagnose PA was evaluated using receiver operating characteristic (ROC) analysis.Results: Initially, an obviously significantly increasing level of serum exosomal circCCDC66 was verified in the PA specimens compared with health controls. Importantly, serum exosomal circCCDC66 which was secreted and released by PA cells could monitor tumor dynamics and serve as potentially prognostic biomarker during treatment. Additionally, ROC curve analysis and the corresponding area under the curve (AUC) values were performed to confirm the ability of serum exosomal circCCDC66 as a potentially diagnostic and prognostic biomarker for PA patients. Importantly, the progression free survival was much longer in low serum exosomal circCCDC66 group compared with the high serum exosomal circCCDC66 group.Serum exosomal circCCDC66 is abnormally elevated and may be served as a promising factor for diagnosis and predicting prognosis in PA patients.